A heat treatment method for improving the fracture toughness of aluminum alloy

By adopting heat treatment methods of homogenization, preheating, solid solution, stretching and secondary aging treatment on the aluminum alloy thick plate, the residual stress problem after quenching of the aluminum alloy thick plate is solved, and its fracture toughness and overall performance are improved.

CN118792600BActive Publication Date: 2025-04-15JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411167386.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-04-15
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The residual stress of the aluminum alloy thick plates during the quenching process leads to a degradation of the subsequent processing and application performance of the material, especially when subjected to alternating loads and corrosive environments, which can easily lead to premature failure or accidents of the material.

Method used

A heat treatment method is adopted, including homogenization treatment, preheating treatment, solid solution treatment, stretching treatment and secondary aging treatment. By controlling the types and content of elements in the aluminum alloy, the fracture toughness of each phase of the aluminum alloy sheet is improved.

Benefits of technology

It effectively improves the fracture toughness of aluminum alloy sheets, reduces residual stress, and improves the overall performance of the material. No matter how the thickness of the sheet changes, good performance can be obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a heat treatment method for improving the fracture toughness of aluminum alloys, and belongs to the technical field of strengthening the mechanical properties of aluminum alloys. The heat treatment method provided by the present invention is to sequentially subject an aluminum alloy plate to homogenization treatment, preheating treatment, solution treatment, stretching treatment, and secondary aging treatment. The present invention effectively improves the fracture toughness of each phase of the aluminum alloy plate by controlling the type and content of elements in the aluminum alloy and a special heat treatment method, and can obtain better performance regardless of the thickness of the plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of strengthening the mechanical properties of aluminum alloys, and in particular to a heat treatment method for improving the fracture toughness of aluminum alloys. Background Art

[0002] Aluminum alloy thick plates are important structural materials in the modern aviation industry, mainly used to produce aircraft fuselages, wings, tails, skins and other parts. These parts are usually made by direct milling of high-strength aluminum alloy thick plates to reduce manufacturing costs, reduce fuselage weight and facilitate management. If the aluminum plate is not thick enough, large parts cannot be cut. For example, the thickest plate required for C919 must reach 200mm, and at the same time, it must meet the performance requirements of corrosion resistance, high strength, fatigue resistance, dimensional stability, and easy machining (polishing, cutting, etc.). The technical threshold is extremely high.

[0003] Aluminum alloy thick plates can be divided into ingot hot-rolled thick plates and cast thick plates from the production process. Among them, although the thickness of the cast thick plate can be unlimited and the maximum thickness can reach 1.2 meters, the performance is much different from that of the ingot hot-rolled thick plate after the rolling process. Therefore, aviation products generally use ingot hot-rolled thick plates. The typical production process of ingot hot-rolled thick plates is: raw materials → casting → ingot milling → hot rolling → solution treatment → quenching → stretching → sawing. Although this set of processes is relatively mature, there is still a fatal problem that directly affects the service life of aluminum alloy thick plate manufacturing parts: during quenching, due to the large difference in temperature between the inside and outside of the plate, when the aluminum plate exceeds 6mm, a large quenching residual stress will be formed. The existence of residual stress seriously affects the subsequent processing and application of the material, especially when used as a structural part that bears alternating loads or works in a corrosive environment, residual stress is a major cause of premature failure of the material and even serious accidents. At present, in order to reduce the residual stress inside the aluminum alloy thick plate, the aluminum alloy plate needs to be subjected to 1% to 3% tensile deformation through a stretching machine after quenching to offset the residual stress.

[0004] In recent years, as the aviation field has further developed in the direction of lightweight, high speed and large-scale, the requirements for the performance of aluminum alloy thick plates and the stability and safety of their manufactured parts have become increasingly higher. A new problem has emerged in the service of aluminum alloy parts: Since the rolling and stretching deformation processes have obvious directionality, the organization and performance of the aluminum alloy thick plates also have directionality, that is, there are obvious differences in the mechanical properties of the aluminum alloy thick plates in different directions, especially the fracture toughness, which is difficult to meet the use requirements of parts such as wings and tail fins that will bear working loads in different directions. Once an accident occurs, the hazard is extremely great. Summary of the invention

[0005] Based on the above content, the purpose of the present invention is to provide a heat treatment method for improving the fracture toughness of aluminum alloy.

[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical solutions: a heat treatment method for improving the fracture toughness of aluminum alloy, wherein the aluminum alloy plate is subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence.

[0007] In some embodiments, the aluminum alloy plate is a continuously cast aluminum alloy plate.

[0008] In some embodiments, the chemical composition of the aluminum alloy plate is, by mass percentage, Zn: 6.3-6.45%, Cu: 2.2-2.45%, Mg: 2.05-2.2%, composite rare earth: 0.02-0.06%, Si: 0-0.05%, Fe: 0-0.06%, Mn: 0-0.015%, Cr: 0-0.025%, Zr: 0.085-0.15%, Ti: 0.01-0.05%, B: 0-0.002%, Na: 0-0.005%, and the balance is Al.

[0009] In some embodiments, the chemical composition of the aluminum alloy plate is, by mass percentage, Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Zr: 0.11%, Ti: 0.02%, B: 0.001%, and the balance is Al.

[0010] In some embodiments, the chemical composition of the composite rare earth is, by mass percentage, Er: 15-20%, Ce: 15-20%, La: 15-20%, Y: 5-10%, Pr: 5-10%, and the remainder is Nd.

[0011] In some embodiments, the chemical composition of the composite rare earth is, by mass percentage, Er: 17%, Ce: 18%, La: 17%, Y: 7%, Pr: 7%, and the remainder is Nd.

[0012] In the present invention, the contents of Fe, Si, Mn and Cr must be strictly controlled to prevent the formation of brittle phases that affect the fracture toughness of aluminum alloys. Ti, B and Zr are mainly used as grain refining elements, and play a role in heterogeneous nucleation in aluminum alloys. Na is an inevitable impurity element. Composite rare earths play a comprehensive role in solid solution strengthening, purifying the melt, refining grains and improving the morphology of grain boundary phases. If added in excess, coarse grain boundary phases will be formed and aggregated into inclusions, which significantly affects the performance of the alloy. Among them, Ce and La have low melting points and are very easy to react with impurities such as H, O, P, and S to form compounds, which mainly play a role in purifying the melt; Y and Er have good plasticity, and the formation of evenly distributed grain boundary phases can improve the plasticity and corrosion resistance of the alloy; Nd and Pr are easy to form grain boundary phases with good heat resistance, which improves the high temperature performance of the alloy.

[0013] In some embodiments, the homogenization treatment is: air cooling after keeping at 460-470°C for a certain time, preferably air cooling after keeping at 465°C for a certain time, and the holding time (Y1, min) and the thickness of the aluminum alloy plate (X, mm) conform to the following rules:

[0014] ①When X∈[80,100], Y1=15×X;

[0015] ②When X∈(100,120], Y1=13.5×X;

[0016] ③When X∈(120,150], Y1=12×X;

[0017] ④When X∈(150,180], Y1=11×X;

[0018] ⑤When X∈(180,200], Y1=10×X.

[0019] The present invention can effectively improve the segregation phenomenon by homogenizing and utilizing the heat diffusion effect, promote more uniform tissue distribution and chemical composition, ensure the composition uniformity of the aluminum alloy plate, and provide a good tissue foundation for subsequent heat treatment.

[0020] In some embodiments, the preheating treatment is: keeping the temperature at 430° C. for a certain period of time, and the preheating time (Y2, min) and the thickness of the aluminum alloy plate (X, mm) conform to the following rules:

[0021] ①When X∈[80,100], Y2=270;

[0022] ②When X∈(100,150], Y2=300;

[0023] ③When X∈(150,180], Y2=360;

[0024] ④When X∈(180,200], Y2=420.

[0025] In the present invention, when the preheating temperature is lower than 430°C, the alloy still has high hardness, the rolling deformation is small and the alloy is easy to crack, which is not conducive to the rolling process; when the preheating temperature is higher than 430°C, the mechanical properties of the alloy are soft, and if the microstructure is not uniform, it will cause local overheating and overburning problems. On the other hand, the surface flatness of the alloy after rolling is poor. The present invention reduces the hardness of the aluminum alloy through preheating treatment to ensure the smooth implementation of the hot rolling process.

[0026] In some embodiments, the solution treatment is: after keeping at 465-475°C for a certain period of time, immediately quench into water at 50-60°C for cooling, preferably after keeping at 470°C for a certain period of time, immediately quench into water at 50-60°C for cooling, and the solution time (Y3, min) and the thickness of the aluminum alloy plate (X, mm) conform to the following rules:

[0027] ①When X∈[80,100], Y3=16×X;

[0028] ②When X∈(100,120], Y3=14.5×X;

[0029] ③When X∈(120,150], Y3=13×X;

[0030] ④When X∈(150,180], Y3=12×X;

[0031] ⑤When X∈(180,200], Y3=11×X.

[0032] In the present invention, when the solution temperature is lower than 465°C, the diffusion rate of each element in the alloy is slow, and a longer insulation time needs to be provided, which reduces the actual production efficiency. In addition, the total amount of solid solution that can be generated in conjunction with the quenching process is insufficient, resulting in a large amount of residual grain boundary compounds and little change in morphology and distribution, which is not conducive to the subsequent improvement of the performance of each phase of the alloy; when the solution temperature is higher than 475°C, although the element diffusion rate is increased and it is more conducive to the generation of more solid solutions, it causes excessive elements to be dissolved into the aluminum alloy lattice, and the lattice distortion is large, which is not conducive to the subsequent rolling process, and it is easy to cause deformation or even cracking of the alloy rolling surface. In addition, if the temperature is too high, there is also a risk of overburning of the alloy grain boundary phase, which affects the mechanical properties of the alloy.

[0033] In some embodiments, the stretching rate of the stretching treatment is 1.5-1.8%, preferably 1.6%. The purpose of the stretching treatment is to remove residual stress. The stretching rate is calculated as:

[0034]

[0035] In the present invention, when the elongation rate is lower than 1.5%, the residual stress is not completely removed, affecting the subsequent aging treatment effect; when the elongation rate is higher than 1.8%, although the residual stress can be effectively removed, the grain structure will be elongated and directional, affecting the performance of different phases of the plate.

[0036] In some embodiments, the secondary aging treatment is: regardless of the thickness of the plate, the primary aging treatment is first carried out at 120-130°C for 5 hours, and then the temperature is raised to 160-170°C with the furnace for a certain time for secondary aging treatment, so that the grain size of the aluminum alloy tends to be stable, so as to further improve the uniformity of the microstructure of plates of different thicknesses. The above aging treatment process is preferably: first carry out primary aging treatment at 125°C for 5 hours, and then carry out secondary aging treatment by raising the temperature to 165°C with the furnace for a certain time. The holding time (Y4, h) and the plate thickness (X, mm) conform to the following rules:

[0037] ①When X∈[80,100], Y4=18;

[0038] ②When X∈(100,150], Y4=20;

[0039] ③When X∈(150,200], Y4=22.

[0040] The present invention discloses the following technical effects:

[0041] The present invention provides a heat treatment method for improving the fracture toughness of aluminum alloys, wherein the aluminum alloy plate is subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. The present invention effectively improves the fracture toughness of each phase of the aluminum alloy plate by controlling the type and content of elements in the aluminum alloy and a special heat treatment method, and can obtain better performance regardless of the thickness of the plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is a schematic diagram of the sampling method of the sample on the thick plate when conducting the fracture toughness experiment in the present invention. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0050] The fracture toughness test in the embodiment is carried out according to GB / T 4161-2007 (Metallic Materials-Plane Strain Fracture Toughness KIC Test Method), and the wire cutting method is used to sample in various directions of the thick plate (such as Figure 1 The fracture toughness tests were performed respectively.

[0051] Example 1

[0052] The thickness of the continuously cast aluminum alloy plate in this embodiment is 80 mm, and the chemical composition is as follows by mass percentage: Zn: 6.3%, Cu: 2.2%, Mg: 2.05%, composite rare earth: 0.02%, Zr: 0.085%, Ti: 0.01%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 15%, Ce is 15%, La is 15%, Y is 5%, Pr is 5%, and the balance is Nd.

[0053] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 460℃ for 1200min. Preheating treatment: keep at 430℃ for 270min. Solution treatment: keep at 465℃ for 1280min and then immediately quench in 50℃ water for cooling. Stretching treatment: the elongation is controlled at 1.5%. Secondary aging treatment: first keep at 120℃ for 5h for primary aging treatment, then heat up to 160℃ with the furnace for 18h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0054] Example 2

[0055] The thickness of the continuously cast aluminum alloy plate in this embodiment is 80 mm, and the chemical composition is as follows by mass percentage: Zn: 6.45%, Cu: 2.45%, Mg: 2.2%, composite rare earth: 0.06%, Si: 0.05%, Fe: 0.06%, Mn: 0.015%, Cr: 0.025%, Zr: 0.15%, Ti: 0.05%, B: 0.002%, Na: 0.005%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 20%, Ce is 20%, La is 20%, Y is 10%, Pr is 10%, and the balance is Nd.

[0056] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 470℃ for 1200min. Preheating treatment: keep at 430℃ for 270min. Solution treatment: keep at 475℃ for 1280min and then immediately quench in 60℃ water for cooling. Stretching treatment: the elongation is controlled at 1.8%. Secondary aging treatment: first keep at 130℃ for 5h for primary aging treatment, then heat up to 170℃ with the furnace for 18h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0057] Example 3

[0058] The thickness of the continuously cast aluminum alloy plate in this embodiment is 80 mm, and the chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0059] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1200min. Preheating treatment: keep at 430℃ for 270min. Solution treatment: keep at 470℃ for 1280min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 18h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0060] Example 4

[0061] The thickness of the continuously cast aluminum alloy plate in this embodiment is 120 mm, and the chemical composition is as follows by mass percentage: Zn: 6.3%, Cu: 2.2%, Mg: 2.05%, composite rare earth: 0.02%, Zr: 0.085%, Ti: 0.01%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 15%, Ce is 15%, La is 15%, Y is 5%, Pr is 5%, and the balance is Nd.

[0062] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 460℃ for 1620min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 465℃ for 1740min and then immediately quench in 50℃ water for cooling. Stretching treatment: the elongation is controlled at 1.5%. Secondary aging treatment: first keep at 120℃ for 5h for primary aging treatment, then heat up to 160℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0063] Example 5

[0064] The thickness of the continuously cast aluminum alloy plate in this embodiment is 120 mm, and the chemical composition is as follows by mass percentage: Zn: 6.45%, Cu: 2.45%, Mg: 2.2%, composite rare earth: 0.06%, Si: 0.05%, Fe: 0.06%, Mn: 0.015%, Cr: 0.025%, Zr: 0.15%, Ti: 0.05%, B: 0.002%, Na: 0.005%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 20%, Ce is 20%, La is 20%, Y is 10%, Pr is 10%, and the balance is Nd.

[0065] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 470℃ for 1620min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 475℃ for 1740min and then immediately quench in 60℃ water for cooling. Stretching treatment: the elongation rate was controlled at 1.8%. Secondary aging treatment: first keep at 130℃ for 5h for primary aging treatment, then heat up to 170℃ with the furnace and keep for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0066] Example 6

[0067] The thickness of the continuously cast aluminum alloy plate in this embodiment is 120 mm, and the chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0068] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1620min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 470℃ for 1740min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0069] Example 7

[0070] The thickness of the continuously cast aluminum alloy plate in this embodiment is 150 mm, and the chemical composition is as follows by mass percentage: Zn: 6.3%, Cu: 2.2%, Mg: 2.05%, composite rare earth: 0.02%, Zr: 0.085%, Ti: 0.01%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 15%, Ce is 15%, La is 15%, Y is 5%, Pr is 5%, and the balance is Nd.

[0071] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 460℃ for 1800min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 465℃ for 1950min and then immediately quench in 50℃ water for cooling. Stretching treatment: the elongation is controlled at 1.5%. Secondary aging treatment: first keep at 120℃ for 5h for primary aging treatment, then heat up to 160℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0072] Example 8

[0073] The thickness of the continuously cast aluminum alloy plate in this embodiment is 150 mm, and the chemical composition is as follows by mass percentage: Zn: 6.45%, Cu: 2.45%, Mg: 2.2%, composite rare earth: 0.06%, Si: 0.05%, Fe: 0.06%, Mn: 0.015%, Cr: 0.025%, Zr: 0.15%, Ti: 0.05%, B: 0.002%, Na: 0.005%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 20%, Ce is 20%, La is 20%, Y is 10%, Pr is 10%, and the balance is Nd.

[0074] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 470℃ for 1800min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 475℃ for 1950min and then immediately quench in 60℃ water for cooling. Stretching treatment: the elongation is controlled at 1.8%. Secondary aging treatment: first keep at 130℃ for 5h for primary aging treatment, then heat up to 170℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0075] Example 9

[0076] The thickness of the continuously cast aluminum alloy plate in this embodiment is 150 mm, and the chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0077] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1800min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 470℃ for 1950min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0078] Example 10

[0079] The thickness of the continuously cast aluminum alloy plate in this embodiment is 180 mm, and the chemical composition is as follows by mass percentage: Zn: 6.3%, Cu: 2.2%, Mg: 2.05%, composite rare earth: 0.02%, Zr: 0.085%, Ti: 0.01%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 15%, Ce is 15%, La is 15%, Y is 5%, Pr is 5%, and the balance is Nd.

[0080] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 460℃ for 1980min. Preheating treatment: keep at 430℃ for 360min. Solution treatment: keep at 465℃ for 2160min and then immediately quench in 50℃ water for cooling. Stretching treatment: the elongation is controlled at 1.5%. Secondary aging treatment: first keep at 120℃ for 5h for primary aging treatment, then heat up to 160℃ with the furnace and keep for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0081] Embodiment 11

[0082] The thickness of the continuously cast aluminum alloy plate in this embodiment is 180 mm, and the chemical composition is as follows by mass percentage: Zn: 6.45%, Cu: 2.45%, Mg: 2.2%, composite rare earth: 0.06%, Si: 0.05%, Fe: 0.06%, Mn: 0.015%, Cr: 0.025%, Zr: 0.15%, Ti: 0.05%, B: 0.002%, Na: 0.005%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 20%, Ce is 20%, La is 20%, Y is 10%, Pr is 10%, and the balance is Nd.

[0083] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 470℃ for 1980min. Preheating treatment: keep at 430℃ for 360min. Solution treatment: keep at 475℃ for 2160min and then immediately quench in 60℃ water for cooling. Stretching treatment: the elongation is controlled at 1.8%. Secondary aging treatment: first keep at 130℃ for 5h for primary aging treatment, then heat up to 170℃ with the furnace and keep for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0084] Example 12

[0085] The thickness of the continuously cast aluminum alloy plate in this embodiment is 180 mm, and the chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0086] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1980min. Preheating treatment: keep at 430℃ for 360min. Solution treatment: keep at 470℃ for 2160min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0087] Embodiment 13

[0088] In this embodiment, the thickness of the continuously cast aluminum alloy plate is 200 mm, and the chemical composition is as follows by mass percentage: Zn: 6.3%, Cu: 2.2%, Mg: 2.05%, composite rare earth: 0.02%, Zr: 0.085%, Ti: 0.01%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 15%, Ce is 15%, La is 15%, Y is 5%, Pr is 5%, and the balance is Nd.

[0089] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 460℃ for 2000min. Preheating treatment: keep at 430℃ for 420min. Solution treatment: keep at 465℃ for 2200min and then immediately quench in 50℃ water for cooling. Stretching treatment: the elongation is controlled at 1.5%. Secondary aging treatment: first keep at 120℃ for 5h for primary aging treatment, then heat up to 160℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0090] Embodiment 14

[0091] The thickness of the continuously cast aluminum alloy plate in this embodiment is 200 mm, and the chemical composition is as follows by mass percentage: Zn: 6.45%, Cu: 2.45%, Mg: 2.2%, composite rare earth: 0.06%, Si: 0.05%, Fe: 0.06%, Mn: 0.015%, Cr: 0.025%, Zr: 0.15%, Ti: 0.05%, B: 0.002%, Na: 0.005%, and the balance is Al. Among them, the chemical composition of the composite rare earth is: Er is 20%, Ce is 20%, La is 20%, Y is 10%, Pr is 10%, and the balance is Nd.

[0092] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 470℃ for 2000min. Preheating treatment: keep at 430℃ for 420min. Solution treatment: keep at 475℃ for 2200min and then immediately quench in 60℃ water for cooling. Stretching treatment: the elongation is controlled at 1.8%. Secondary aging treatment: first keep at 130℃ for 5h for primary aging treatment, then heat up to 170℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0093] Embodiment 15

[0094] In this embodiment, the thickness of the continuously cast aluminum alloy plate is 200 mm, and the chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0095] The continuous casting aluminum alloy plate was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 2000min. Preheating treatment: keep at 430℃ for 420min. Solution treatment: keep at 470℃ for 2200min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0096] Comparative Example 1

[0097] The material in this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 80 mm. The chemical composition by mass percentage is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0098] The 7075 aluminum alloy sheet was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1200min. Preheating treatment: keep at 430℃ for 270min. Solution treatment: keep at 470℃ for 1280min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 18h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0099] Comparative Example 2

[0100] The material in this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 120 mm. The chemical composition by mass percentage is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0101] The 7075 aluminum alloy sheet was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1620min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 470℃ for 1740min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0102] Comparative Example 3

[0103] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 150 mm. The chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0104] The 7075 aluminum alloy sheet was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1800min. Preheating treatment: keep at 430℃ for 300min. Solution treatment: keep at 470℃ for 1950min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 20h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0105] Comparative Example 4

[0106] The material in this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 180 mm. The chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0107] The 7075 aluminum alloy sheet was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 1980min. Preheating treatment: keep at 430℃ for 360min. Solution treatment: keep at 470℃ for 2160min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0108] Comparative Example 5

[0109] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 200 mm. Its chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0110] The 7075 aluminum alloy sheet was subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence. Among them: Homogenization treatment: keep at 465℃ for 2000min. Preheating treatment: keep at 430℃ for 420min. Solution treatment: keep at 470℃ for 2200min and then immediately quench in 55℃ water for cooling. Stretching treatment: the elongation is controlled at 1.6%. Secondary aging treatment: first keep at 125℃ for 5h for primary aging treatment, then heat up to 165℃ with the furnace for 22h for secondary aging treatment. After completing all the above heat treatment processes, the fracture toughness test was carried out, and the experimental results are shown in Table 1.

[0111] Comparative Example 6

[0112] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 80 mm. Its chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0113] The 7075 aluminum alloy sheet was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0114] Comparative Example 7

[0115] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 120 mm. Its chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0116] The 7075 aluminum alloy sheet was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0117] Comparative Example 8

[0118] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 150 mm. The chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0119] The 7075 aluminum alloy sheet was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0120] Comparative Example 9

[0121] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 180 mm. Its chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0122] The 7075 aluminum alloy sheet was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0123] Comparative Example 10

[0124] The material of this comparative example is a commercially available 7075 aluminum alloy plate with a thickness of 200 mm. Its chemical composition, by mass percentage, is: Zn: 5.6%, Cu: 1.6%, Mg: 2.5%, Cr: 0.23%, Si: 0.2%, Fe: 0.25%, Mn: 0.15%, Ti: 0.02%, other elements ≤ 0.15% (including a single element ≤ 0.05%), and the balance is Al.

[0125] The 7075 aluminum alloy sheet was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0126] Comparative Example 11

[0127] The material of this comparative example is a continuously cast aluminum alloy plate with a thickness of 80 mm. The chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0128] The continuously cast aluminum alloy plate was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0129] Comparative Example 12

[0130] The material of this comparative example is a continuously cast aluminum alloy plate with a thickness of 120 mm. The chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0131] The continuously cast aluminum alloy plate was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0132] Comparative Example 13

[0133] The material of this comparative example is a continuously cast aluminum alloy plate with a thickness of 150 mm. The chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0134] The continuously cast aluminum alloy plate was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0135] Comparative Example 14

[0136] The material of this comparative example is a continuously cast aluminum alloy plate with a thickness of 180 mm. The chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0137] The continuously cast aluminum alloy plate was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0138] Comparative Example 15

[0139] The material of this comparative example is a continuously cast aluminum alloy plate with a thickness of 200 mm. The chemical composition is as follows by mass percentage: Zn: 6.4%, Cu: 2.3%, Mg: 2.1%, composite rare earth: 0.04%, Ti: 0.02%, B: 0.001%, Zr: 0.11%, and the balance is Al. Among them, the chemical composition of the composite rare earth is as follows by mass percentage: Er is 17%, Ce is 18%, La is 17%, Y is 7%, Pr is 7%, and the balance is Nd.

[0140] The continuously cast aluminum alloy plate was subjected to solution treatment and aging treatment in sequence. Solution treatment: 500℃ for 8h, then immediately cooled to room temperature. Aging treatment: 180℃ for 12h, then air cooled. The mechanical properties of the aluminum alloy prepared by the above process were tested, and the experimental results are shown in Table 1.

[0141] The experimental results of Examples 1-15 and Comparative Examples 1-15 are shown in Table 1. It can be seen that, compared with the commonly used 7075 aluminum alloy and the solution + aging heat treatment currently used by enterprises, the method of the present invention can effectively improve the fracture toughness of each phase of the aluminum alloy plate, and regardless of how the thickness of the plate changes, better performance can be obtained.

[0142] Table 1 Mechanical properties of aluminum alloy sheets with different thicknesses

[0143]

[0144]

[0145] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A heat treatment method for reducing the difference in fracture toughness of each phase of an aluminum alloy plate, characterized in that: The aluminum alloy plate is subjected to homogenization treatment, preheating treatment, solution treatment, stretching treatment and secondary aging treatment in sequence; The chemical composition of the aluminum alloy plate is as follows by mass percentage: Zn: 6.3-6.45%, Cu: 2.2-2.45%, Mg: 2.05-2.2%, composite rare earth: 0.02-0.06%, Si: 0-0.05%, Fe: 0-0.06%, Mn: 0-0.015%, Cr: 0-0.025%, Zr: 0.085-0.15%, Ti: 0.01-0.05%, B: 0-0.002%, Na: 0-0.005%, and the balance is Al; The chemical composition of the composite rare earth is: Er: 15-20%, Ce: 15-20%, La: 15-20%, Y: 5-10%, Pr: 5-10%, and the balance is Nd; The homogenization treatment is: heat preservation at 460-470°C for a certain period of time and then air cooling, and the heat preservation time Y1 and the thickness X of the aluminum alloy plate conform to the following rules: ①When X∈[80,100], Y1=15×X; ②When X∈(100,120], Y1=13.5×X; ③When X∈(120,150], Y1=12×X; ④When X∈(150,180], Y1=11×X; ⑤When X∈(180,200], Y1=10×X; Among them, the measurement unit of the holding time Y1 is min, and the measurement unit of the aluminum alloy plate thickness X is mm; The preheating treatment is: keeping the temperature at 430°C for a certain period of time; the holding time Y2 and the thickness X of the aluminum alloy plate conform to the following rules: ①When X∈[80,100], Y2=270; ②When X∈(100,150], Y2=300; ③When X∈(150,180], Y2=360; ④When X∈(180,200], Y2=420; Among them, the measurement unit of the holding time Y2 is min, and the measurement unit of the aluminum alloy plate thickness X is mm; The solution treatment is: after keeping at 465-475°C for a certain period of time, immediately quench in water at 50-60°C for cooling. The keeping time Y3 and the thickness X of the aluminum alloy plate conform to the following rules: ①When X∈[80,100], Y3=16×X; ②When X∈(100,120], Y3=14.5×X; ③When X∈(120,150], Y3=13×X; ④When X∈(150,180], Y3=12×X; ⑤When X∈(180,200], Y3=11×X; Among them, the measurement unit of the holding time Y3 is min, and the measurement unit of the aluminum alloy plate thickness X is mm; The stretching rate of the stretching treatment is 1.5 to 1.8%; The secondary aging treatment is: first keep the temperature at 120-130°C for 5 hours, then heat up to 160-170°C with the furnace and keep the temperature for a certain period of time. The holding time Y4 and the thickness X of the aluminum alloy plate conform to the following rules: ①When X∈[80,100], Y4=18; ②When X∈(100,150], Y4=20; ③When X∈(150,200], Y4=22; Among them, the measurement unit of the insulation time Y4 is h, and the measurement unit of the aluminum alloy plate thickness X is mm.

2. The heat treatment method for reducing the difference in fracture toughness of each phase of the aluminum alloy sheet according to claim 1, characterized in that: The aluminum alloy plate is a continuously cast aluminum alloy plate.

Citation Information

Patent Citations

  • Manufacturing method of aviation aluminum alloy profiles

    CN103103424A

  • A method for manufacturing an aluminum alloy section bar used for aviation

    CN108165848A

  • High strength 7xxx aluminum alloys and methods of making the same

    CN110453122A